A New Generation of Glycoconjugated Azo Dyes Based on Aminosugars. (29th July 2015) - Guazzelli, Lorenzo; Catelani, Giorgio; D'Andrea, Felicia
Abstract : The third generation of glycoconjugated azo dyes (GADs) was prepared linking monoazo dyes to 6-amino-6-deoxy-d -galactose or 6′amino-6′-deoxylactose through mixed amido-ester connections. The complementary conjugation reactions were studied using the succinyl derivative of either the acetal protected aminosugar or the azo dye. Target "naturalized" GADs were obtained after acid hydrolysis of the acetal protecting groups present on the sugar moiety.